(untitled) (Oxford, 1978)
Covers all aspects of twentieth-century technology, including developments which are essentially products of this century, such as aeronautics and computers, as well as those that have roots in the past. While the emphasis is on technological innovation, attention is directed also to the social, economic, and political factors influencing recent industrial developments.
Keywords: Công nghệ,Technology; Lịch sử,History